Origins of the seed: The “golden-trio hypothesis” - Bai, Shu-Nong; Rao, Guang-Yuan; Yang, Ji (Frontiers in Plant Science, 2022)
The seed is an evolutionary innovation in the plant kingdom. While human civilization depends heavily on seed production, how the seed trait emerged remains elusive. In this opinion article, The “golden-trio hypothesis” was proposed based on our investigations of LEC1 gene functions in Adiantum capillus-veneris. This hypothesis suggests that a “seed program” arose from spatiotemporal integration of three key components: assimilate flow, ABA-mediated stress responses, and stress-induced LEC1 expression. Thus, the evolutionary innovation of seeds is not a simple event resulting from new genes; rather, it should be considered the outcome of a series of physiological and morphological innovations that emerged prior to and regardless of the origin of the seed program. This new perspective sheds light on the puzzling origin of seeds.